Analysis of fire deaths in Poland and influence of smoke toxicity. (August 2017) - Giebułtowicz, Joanna; Rużycka, Monika; Wroczyński, Piotr; Purser, David A.; Stec, Anna A.
Highlights: Findings from 263 dwelling fire death cases (2003–2011) in central Poland have been reported. The majority of victims were in the room of origin, around half were found close to burned furniture. The majority of victims had inhaled sufficient CO and other gases to cause incapacitation. Approximately 80% of victims were identified with the soot in their airways. Around 60% had inhaled sufficient CO and other gases to contribute to or be the main cause of death. Abstract: Dwelling fires have changed over the years because building contents and the materials used in then have changed. They all contribute to an ever-growing diversity of chemical species found in fires, many of them highly toxic. These arise largely from the changing nature of materials in interior finishes and furniture, with an increasing content of synthetic materials containing higher levels of nitrogen, halogen and phosphorus additives. While there is still a belief that carbon monoxide is the major lethal toxic agent in fires, the hydrogen cyanide and acid gases released from these additives are now well-recognised as major contributory causes of incapacitation, morbidity and mortality in domestic fires. Data for the total number of 263 fire death cases in the Mazowieckie region (mainly Warsaw area) of Poland between 2003–2011 for dwellings fires were obtained from pathologists, forensic toxicologists, fire fighters and analysed. Factors contributing to the death such as the findings of the full post mortem examination (age, sex, health status, burns), the toxicological analysis (carbon monoxide, alcohol etc.), and a thorough investigation of the scene (fire conditions, fuel, etc.) were taken into account and are summarised.